Multiple Human Papillomavirus Infections among Chinese Women with and without Cervical Abnormalities: A Population-Based Multi-Center Cross-Sectional Study - LI, Ni; YANG, Lin; ZHANG, Kai; ZHANG, Yawei; ZHENG, Tongzhang; DAI, Min (Frontiers in Oncology, 2011)
Abstract: Background: Despite an increase in the number of studies conducted in recent years on HPV and cervical cancer epidemiology, the profile of multiple HPV infections remains obscure, particularly among Chinese women. Based on a series of population-based HPV prevalence surveys among Chinese women, we evaluated the prevalence and risk factors of multiple HPV infections, and explored its association with cervical abnormalities. Methods: A total of 2374 women from three study centres underwent gynaecological examinations with valid cytology and their HPV results were included in the analysis. Forty-four HPV types were detected using the GP5+/6+ PCR-based enzyme immunoassay. An unconditional logistic regression model was used to evaluate the effect of multiple HPV infections on cervical lesions and its risk factors. The between-groups difference was evaluated by a heterogeneity test based on the Q test. Results: One hundred and eleven women of multiple HPV infections was found among 2374 Chinese women with a prevalence of 5.28% (95%CI=3.86%-5.60%), which attributed to 28.98% (95%CI=24.49%-33.81%) of all of the 383 HPV positive women. A significantly increased risk of multiple HPV infections was found in the older women (≥45 years) (adjusted OR=1.52, 95%CI=1.02-2.27) and those having more than 3 sexual partners (adjusted OR=2.10, 95%CI=1.05-4.17) after adjustment for age-group, study area, and number of sexual partner. We also found that the risk of high-grade lesions was significantly higher than that of low-grade lesions with the multiple HPV infections (P heterogeneity= 0.044), but not as significantly with the single HPV infection (P heterogeneity= 0.108). Conclusions: Multiple HPV Infections, especially with high-risk HPV types, may be a substantial indicator either for public cervical cancer prevention or clinical implications.